2022
DOI: 10.3389/fnagi.2022.830569
|View full text |Cite
|
Sign up to set email alerts
|

Iron Dyshomeostasis and Ferroptosis: A New Alzheimer’s Disease Hypothesis?

Abstract: Iron plays a crucial role in many physiological processes of the human body, but iron is continuously deposited in the brain as we age. Early studies found iron overload is directly proportional to cognitive decline in Alzheimer’s disease (AD). Amyloid precursor protein (APP) and tau protein, both of which are related to the AD pathogenesis, are associated with brain iron metabolism. A variety of iron metabolism-related proteins have been found to be abnormally expressed in the brains of AD patients and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 202 publications
(246 reference statements)
1
47
0
Order By: Relevance
“…Similar to our previous study, the up-regulation of intracellular iron was reversed by KD treatment ( Wang X. et al, 2022 ). What’s more, it has been demonstrated that iron accumulation can worsen senile plaque deposition and promote tau phosphorylation ( Wang F. et al, 2022 ). More β-secretase is activated in the presence of excessive iron and then accelerating the Aβ production and amyloid deposition ( Ayton et al, 2020 ; Gleason and Bush, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our previous study, the up-regulation of intracellular iron was reversed by KD treatment ( Wang X. et al, 2022 ). What’s more, it has been demonstrated that iron accumulation can worsen senile plaque deposition and promote tau phosphorylation ( Wang F. et al, 2022 ). More β-secretase is activated in the presence of excessive iron and then accelerating the Aβ production and amyloid deposition ( Ayton et al, 2020 ; Gleason and Bush, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds 15 and 18 were identified in the screening as Fe 2+ ions chelators ( Figure 5 ). This might be an advantageous feature of potential anti-neurodegenerative agents considering the correlation between iron overload, inflammation and glycolysis being inherent components of AD pathogenesis [ 58 ]. Therefore, the growing number of iron-chelating compounds with potential disease-modifying efficacy and the availability of MRI and CSF biomarkers of iron load encourage a deeper exploration of this therapeutic class in AD [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Early research discovered that Alzheimer’s disease’s cognitive deterioration is directly correlated with iron excess. What is more, both APP and tau protein are connected with iron metabolism [ 20 ]. Iron participates in the creation of neurotransmitters, myelination, and antioxidant enzyme activity in the brain [ 21 ].…”
Section: Pathology Of Admentioning
confidence: 99%